2003
DOI: 10.1385/ir:27:2-3:469
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Mammary Tumor Virus and the Immune System

Abstract: Mouse mammary tumor virus (MMTV) is a nonacute transforming retrovirus that causes mammary tumors in susceptible strains of mice. Upon milk-borne transmission, B cells in the gut become infected and subsequently present a virus-encoded superantigen to cognate T cells. These T cells become activated and, in turn, stimulate neighboring lymphocytes, thereby establishing an infection-competent reservoir of lymphoid cells. During puberty and pregnancy, mammary epithelial cells actively divide, and viral transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…Expression is needed for exogenous MMTVs to stimulate cell proliferation of target lymphocytes that allow efficient infection as they transfer from gut to mammary gland after infection with a milk-borne virus. When expressed from an ERV and presented with the correct major histocompatibility complex molecule, it can lead to depletion of specific T-cell subsets, sometimes corresponding to 30% of the mature T-cells of the mouse by a mechanism involving stimulation and apoptosis (162). The absence of target T-cells has the effect of rendering such mice resistant to infection by an exogenous MMTV carrying the same sag gene, but does not appear to compromise immunity to other pathogens (163).…”
Section: Erv Protein Domesticationsmentioning
confidence: 99%
“…Expression is needed for exogenous MMTVs to stimulate cell proliferation of target lymphocytes that allow efficient infection as they transfer from gut to mammary gland after infection with a milk-borne virus. When expressed from an ERV and presented with the correct major histocompatibility complex molecule, it can lead to depletion of specific T-cell subsets, sometimes corresponding to 30% of the mature T-cells of the mouse by a mechanism involving stimulation and apoptosis (162). The absence of target T-cells has the effect of rendering such mice resistant to infection by an exogenous MMTV carrying the same sag gene, but does not appear to compromise immunity to other pathogens (163).…”
Section: Erv Protein Domesticationsmentioning
confidence: 99%
“…MMTV is a pathogen that subverts the immune system, and several strategies of viral host exploitation have been described (Acha-Orbea et al, 2007;Czarneski et al, 2003). The virus enters through Peyer's patches (PP), where it infects B cells and dendritic cells (DCs).…”
Section: Introductionmentioning
confidence: 99%
“…These infected cells present a viral superantigen (SAg) to T cells expressing SAg-specific T-cell receptor Vb chains. The resulting interaction causes a strong immune response that is critical for virus amplification (Cabrera et al, 2008;Czarneski et al, 2003;Held et al, 1994). Many experiments have shown that MMTV infection is not efficient in mice that do not generate an immune response to the SAg due to a deficiency in certain genes or cells (Beutner et al, 1996;Golovkina et al, 1992Golovkina et al, , 1993Held et al, 1993Held et al, , 1994.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting interaction is critical since it leads to the amplification of infection in lymphoid cells and induces the proliferation of infected B cells (21). Infected lymphocytes then carry MMTV to the mammary gland, allowing the virus to be passed to the next generation (1,13). In addition, it has been demonstrated that MMTV interacts with Toll-like receptor 4 (38), and we have shown that this interaction induces recruitment of dendritic cells (DCs) to the PP and increases the expression of the MMTV cell entry receptor on DCs in vivo (8).…”
mentioning
confidence: 99%